THE DEVELOPMENT OF NECESSARY SKILLS FOR SOCIALLY RESPONSIBLE LEARNING PROCESS THROUGH DEBATING - Ročāne, Maija; Samuseviča, Alīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Through the learning process the community's experience is taken over. Nowadays, the close link between a school and the society reinforces the need to improve knowledge and develop life-long learning skills. Successful learning process contributes to the successful development of the society. Thus, socially responsible learning gains significance. Respecting the diversity of views, self-education and research as a productive cognitive process, innovative ideas and implementing projects contribute to socially responsible learning. The effectiveness of the method debating in the learning process is ensured by the fact that debating highlights the topical issues of the society, contributing to a situation in which a young person understands the necessity of the learning content. Socially responsible learning provides the development and targeted acquisition of social and civic skills, learning to learn skills, and communication skills. Giving students the possibility of joining the debating society within the school, not only the students' learning achievements, but also their civic participation have been promoted.